Electrodynamics and 528 Frequency Resonance in Water Science Helps Solve the Mystery in Homeopathy - Horowitz, Leonard G. (Homœopathic Links, 2019)
Scientific advances have increasingly credited water and its messaging capacity to explain many mysteries. Physical-chemical phenomena from genetic functions to intercellular communications have been found to rely on water structuring. Homeopathic researchers now advance related theories including quantum electrodynamics to solve the mystery of this profession's efficacy. Sceptics, however, continue to plague this healing profession. This article examines a generally overlooked foundational feature of water, its structuring and frequency electrodynamics that best explains the mysterious efficacy of homeopathy as well as why reproducibility in experimental outcomes are often unreliable. The ‘key’ that unlocks doors of understanding and demystifying this matter is the frequency central to giving life, sustaining health and rejuvenating nature—the oxygenating energy of 528-nm greenish-yellow light and its sonoluminescent predecessor-in-interest, 528-Hz frequency of sound. Quoting Hermes Trismegistus, ‘As above, so below, as within, so without, as the universe, so the soul…’. This article considers the consciousness and intentionality of homeopaths versus sceptics. This author proposes that the foundation of homeopathy and the solution to its mystery may be the ‘MI’ frequency of the original Solfeggio musical scale reputed to produce miracles, that is, 528 Hz.
Keywords: homeopathy mystery; frequency resonance; water science; 528 energy